Pengaruh Strategi Think Pair Share (TPS) Terhadap Kemampuan Pemecahan Masalah Ekologi Dengan Gaya Kognitif Berbeda - Amiruddin Kasim (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
This study aims to examine differences in ecological problem-solving abilities between groups of students who are taught with TPS cooperative learning strategies and groups of students who are taught using direct learning strategies, to examine differences in ecological problem-solving abilities between groups of students who have field independent cognitive style and field dependent cognitive style. learners, explains the interaction between learning strategies and cognitive styles on the ability of ecological problem solving in learners. The research method used was a quasi-experimental research method with a 2x2 factorial design and data analysis using 2-way ANOVA. The research subjects were 80 students of the Biology Education Study Program consisting of 2 classes (treatment class and control class). The results showed that there was a significant difference in the problem-solving ability of the group of students who were taught using the TPS learning strategy compared to the group of students who were taught using direct learning strategies. The ability to solve ecological problems in the group of students taught with TPS learning strategies was higher than that in the group of students who were taught with direct learning strategies, there was a significant difference in problem-solving abilities between the group of students who had the FI cognitive style and the group of students who had the cognitive style of FD. Students who have a FI cognitive style have a higher ecological problem solving ability than a group of students who have a FD cognitive style. There is no interaction between learning strategies and cognitive styles on students' ecological problem-solving abilities. This shows that the TPS cooperative learning strategy is not influenced by the cognitive style of the learner's ecological problem solving abilities.